Patient perspectives on treating psoriasis with classic inpatient dithranol therapy: a retrospective patient survey. (November 2015) - Painsi, Clemens; Patscheider, Michael; Inzinger, Martin; Lange‐Asschenfeldt, Bernhard; Quehenberger, Franz; Wolf, Peter
Summary: Background: Evidence of the efficacy of dithranol and patient perspectives on the treatment is scant. Patients and Methods: Using a telephone interview survey, we collected retrospective data from 63 patients (41 men [65.1 %] and 22 women [34.9 %]) who had been treated with classic inpatient dithranol (CID). PsoRA (www.psoriasisregistry.at ) was used to obtain clinical data and treatment responses, which were then correlated with the interview responses. Results: Fifty‐two (82.5 %) patients achieved a PASI75 and 51 (81 %) a PASI90 response within a median of 12.5 (range: 3 to 25) days. Ten out of twelve (83 %) patients showed a satisfactory response to CID (PASI75 or greater reduction) despite the fact that they had previously failed to adequately respond to methotrexate, oral retinoids, cyclosporine, or ustekinumab. Overall, patients recalled a median recurrence‐free interval of four (95 % CI: 3–9) months after responding to CID, which was positively correlated with the patients' recommendation of (p = 0.018) and their overall high satisfaction with the treatment (p = 0.012). Conclusions: Despite the known limitations of CID, this survey indicates that dithranol remains a highly efficacious and valuable treatment option as induction therapy in psoriasis. CID can be effective in patients who have failed to respond to systemic therapy, including traditional agents and biologics.